Inactivation of SARS-CoV-2 virus in saliva using a guanidium based transport medium suitable for RT-PCR diagnostic assays. - Sukalyani Banik; Kaheerman Saibire; Shraddha Suryavanshi; Glenn Johns; Soumitesh Chakravorty; Robert Kwiatkowski; David Alland; Padmapriya P Banada (PLoS ONE)
Background Upper respiratory samples used to test for SARS-CoV-2 virus may be infectious and present a hazard during transport and testing. A buffer with the ability to inactivate SARS-CoV-2 at the time of sample collection could simplify and expand testing for COVID-19 to non-conventional settings. Methods We evaluated a guanidium thiocyanate-based buffer, eNAT™ (Copan) as a possible transport and inactivation medium for downstream Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) testing to detect SARS-CoV-2. Inactivation of SARS-CoV-2 USA-WA1/2020 in eNAT and in diluted saliva was studied at different incubation times. The stability of viral RNA in eNAT was also evaluated for up to 7 days at room temperature (28°C), refrigerated conditions (4°C) and at 35°C. Results SARS-COV-2 virus spiked directly in eNAT could be inactivated at >5.6 log10 PFU/ml within a minute of incubation. When saliva was diluted 1:1 in eNAT, no cytopathic effect (CPE) on VeroE6 cells was observed, although SARS-CoV-2 RNA could be detected even after 30 min incubation and after two cell culture passages. A 1:2 (saliva:eNAT) dilution abrogated both CPE and detectable viral RNA after as little as 5 min incubation in eNAT. SARS-CoV-2 RNA from virus spiked at 5X the limit of detection remained positive up to 7 days of incubation in all tested conditions. Conclusion eNAT and similar guanidinium thiocyanate-based media may be of value for transport, stabilization, and processing of clinical samples for RT-PCR based SARS-CoV-2 detection.